Drug release from liposome coated hydrogels for soft contact lenses: the blinking and temperature effect - Paradiso, P. (2018)
This is the accepted version of the following article: J Biomed Mater Res B Appl Biomater. 2017 Oct;105(7):1799-1807, which has been published in final form at http://dx.doi.org/10.1002/jbm.b.33715. This article may be used for non-commercial purposes in accordance with the Wiley Self-Archiving Policy [http://olabout.wiley.com/WileyCDA/Section/id-820227.html].